Effectiveness Of E-Learning on Micro-Entrepreneurs For English Language Training In Tomok Village - Agnes Simbolon, Amelia; Alfira Isya Nabila; Joys Andrean Mardohar Sitanggang; Nabila Amanda Sabrina; Shinta Melina Sidabutar; Anisa Jimina Sinaga; Juli Rachmadani Hasibuan (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This study investigates the impact of an e-learning-based English language training program on micro-entrepreneurs in Tomok Village, Indonesia. With tourism rapidly expanding in the Asia Pacific region, English proficiency is essential for businesses to interact effectively with foreign tourists. The study employs the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation) to assess the effectiveness of the training program. Data were collected through questionnaires, interviews, and pre- and post-tests involving 30 micro-entrepreneurs. The results indicate significant improvements in participants' English proficiency, as evidenced by increased post-test scores compared to pre-test results. Furthermore, participants expressed a strong preference for the flexibility of e-learning, which allows them to learn while managing their businesses. This research highlights the potential of e-learning to enhance micro-entrepreneurs' communication skills in tourism settings, thereby increasing their economic prospects.